PERFOMANCE OF RESILIENT MODULUS AND FATIGUE OF ASPHALTIC CONCRETE WEARING COURSE (AC-WC) CONSIST OF SUPRACOAT ASPHALT - (NIM 250 05 038), Mukhlis
Abstract : The high stiffnes of Asphaltic Concrete tends to place it on the top layer of pavement as the Wearing Course (AC-WC). The damage on the layer was caused by high temperature level and high intensity of traffic loading.The defects reflected on the pavement surface are stripping and surface cracking. The Supracoat Asphalt was then used to enhance that problem . The Laboratory work was conducted to examine the properties of Supracoat asphalt and compare it with the properties of Asphalt Pen 60/70. The properties of Asphaltic Concrete mix (AC-WC) was examined also, using those two types of asphalt. Another complimentary test, i.e. Flexure Fatigue test and UMATTA test were conducted to investigate the fatigue characteristic and to measure Resilient Modulus of mix, respectively. The result of test on asphalt characteristics showed that Supracoat has a lower penetration ( 56,2 mm) than Pen 60/70 (65,8 mm), has higher Viscosity (155 C ) than the Pen 60/70 (152 C) and has higher softening point (51,5 C) than the Pen 60/70 (48,5 C). The change of Softening Point value after RTFOT showed that the Supracoat has a resistance of ageing better that the Pen 60/70. The value of OBC of the mixture using Supracoat and asphalt Pen 60/70 was 5,4% and 4,98% respectively. The marshall characteristic test of Asphalt Concrete mix (AC-WC) using Supracoat gave better result than the mix using asphalt Pen 60/70, shown by these values i.e. VIM (4,18% to 5,37%), VFA (72,69% to 65,51%) and IKS (93,3% to 90,16%). Another test result confirmed those characteristic i.e. higher Resilient Modulus (2996 MPa to 2417 MPa) and higher fatigue life (6331 cycles to 4450 cycles).